Exploring the Use of Social Media in Science Learning Environments: A Systematic Literature Review - Pinky Kusuma Ningtyas; Hayuni Retno Widarti; Parlan Parlan (Journal of Science Learning, 2024)
Social media is one of the platforms that is popular and familiar to various circles. This technology has penetrated multiple fields, especially education. Many studies have shown the use of social media in the learning process. This study aims to explore the use of social media in science learning environments and their impacts. The method used is a Systematic Literature Review with several stages: Identification, Screening, and Inclusion. This systematic literature review used several databases, including Springer, Wiley, and Eric. The study was limited to the last eight years, from 2016 to 2023. After screening using the PRISMA method, 30 articles were obtained and used as literature material. The study results show that social media can be one of the media used in learning science. Social media, which are often used in learning, include Facebook, Instagram, YouTube, Twitter, and WhatsApp. Science learning that requires visualization is suitable if learned using social media. The use of social media in this learning also needs to be adjusted to the characteristics and features owned. The findings in the article report that social media positively affects collaboration skills, knowledge, motivation, and student-centered learning. However, there are negative impacts of using social media that disrupt privacy. In addition, there is a need for training at each institution so that the use of social media is more optimal.